Implementation of GASING Stock Gamification to Increase Financial Literacy for High School Students - Kurniasari, Florentina (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
Financial inclusion played an essential role in increasing the nation's welfare. Therefore, it is crucial to increase financial literacy since the literacy index in Indonesia is still 38,03%. Stock market investment had the lowest contribution toward the level of literacy index. The advancement of ICT and the penetration of internet users support the spreading of financial information among the young generation. Due to its low literacy rate, Indonesians are still vulnerable to false financial information, leading to investment fraud. Gamification is chosen as an alternative method in taking advantage of interactive game development that can easily download via smartphone. The gamification system design, which is named GASING, gives the younger generation adequate information related to secure financial investment. The target game user of GASING is high-school students. The feature of the GASING that offer attractive UI/UX design was expected to increase the knowledge of high-school students in learning stock investment. The usage of GASING gamification was also expected to increase more young generation participation in the Indonesian capital market while simultaneously increasing their knowledge, skills, and confidence in the stock market.